2004
DOI: 10.1093/rpd/nch338
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose to premature infants in neonatal intensive care units in kuwait

Abstract: Entrance surface dose (ESD) and effective dose (E) to premature infants were estimated at three neonatal intensive care units in Kuwait for three standard X-ray examinations--abdominal, chest and skull X rays using a simple water phantom. The ESD was found to vary between 58 and 102 microGy for abdominal X rays, between 51 and 102 microGy for chest X rays and between 58 and 145 microGy for skull examinations. These doses are comparable to the entrance skin doses published elsewhere. The E-values were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
1
17
0
3
Order By: Relevance
“…Negative correlation between HVL of the X-ray beam and ESD during X-ray examinations of premature infants has been reported [29] . The HVL can be raised by increasing either the voltage of the X-ray beam or the total fi ltration of the X-ray unit.…”
Section: Discussionmentioning
confidence: 95%
“…Negative correlation between HVL of the X-ray beam and ESD during X-ray examinations of premature infants has been reported [29] . The HVL can be raised by increasing either the voltage of the X-ray beam or the total fi ltration of the X-ray unit.…”
Section: Discussionmentioning
confidence: 95%
“…Olgar et al also used TLD for measuring ESDs, their results showed that neonates received acceptable doses from common radiological examinations in Turkey (8). Brindhaban et al reported the birth weight range was between 750 and 2000gr for infants (12). However, in this study, the mean ESD for chest and abdomen examination were 76.3 µGy and 61.5µGy, respectively; also DRLs for neonates in our province were 88 µGy for chest and 98µGy for abdomen examinations that were slightly higher than other studies; European national diagnostic reference levels of 80 µGy for mobile chest radiographs and the NRPB reference dose of 50 µGy for chest examination.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows the E levels of various conventional radiologic procedures in adults, children, and neonates. 6,7,10,17,[30][31][32] This comparison is only an approximation, because even for the same radiologic procedure, dose levels are directly related to variations in equipment and depend on age. Nevertheless, conventional radiographs impose a relatively low level of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…4 Tables 7 and 8 show the cancer mortality risk for our cohort of VLBW infants, on the basis of the highest risk level of 13 ϫ 10 Ϫ2 /Sv Ϫ1 , findings similar to those previously reported. 6,7,9,21,40 We also determined risk factors for preterm infants associated with radiographic exposure of specific body regions. 7,10,31 Cancer mortality rates after radiation exposure during childhood (age not further classified) have been reported to be 1:1 000 000 for a thorax radiograph (E Ͻ50 Sv) and 1:100 000 for an abdominal radiograph (E Ͻ100 Sv).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation